1981
DOI: 10.1159/000123147
|View full text |Cite
|
Sign up to set email alerts
|

GABA and Muscimol Inhibit the Release of Prolactin from Dispersed Rat Anterior Pituitary Cells

Abstract: Prolactin release from columns of dispersed rat anterior pituitary cells was inhibited by GABA and the GABA agonist muscimol. The log dose-response curves for GABA and muscimol appeared to be parallel, but were not parallel to that for dopamine. Two GABA antagonists, bicuculline and picrotoxin, blocked the action of both GABA and muscimol, but the dopamine antagonists metoclopramide and perphenazine did not. The data suggest that there are specific GABA receptors on pituitary lactotrophs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 15 publications
(31 reference statements)
1
15
0
Order By: Relevance
“…GABA A and B receptors have been described in the anterior pituitary gland [21,22], and GABA A agonists have been shown to inhibit PRL release at the adenohypophyseal level [10,11,28,29], Interestingly, and for the first time, a significant inhibition of PRL release by adenohypophyseal cultured cells was found in the present experimens with the GABA B receptor agonist baclofen. This basal inhibition was observed after 1 and 2 h of incu bation, though it was not clearly concentration depen dent.…”
Section: Discussionsupporting
confidence: 57%
“…GABA A and B receptors have been described in the anterior pituitary gland [21,22], and GABA A agonists have been shown to inhibit PRL release at the adenohypophyseal level [10,11,28,29], Interestingly, and for the first time, a significant inhibition of PRL release by adenohypophyseal cultured cells was found in the present experimens with the GABA B receptor agonist baclofen. This basal inhibition was observed after 1 and 2 h of incu bation, though it was not clearly concentration depen dent.…”
Section: Discussionsupporting
confidence: 57%
“…GABA has been found to affect the release of prolactin [6,9,10,15,19,24,25,29], LH [ 19,20] and growth hormone [31]. In the case of prolactin the effect of GABA appears to be a direct action at the level of the anterior pituitary [6,9,10, 29] via specific GABA receptors [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of prolactin the effect of GABA appears to be a direct action at the level of the anterior pituitary [6,9,10, 29] via specific GABA receptors [9]. These results have suggested that GABA is released from the hypothalamus in to the portal system.…”
Section: Discussionmentioning
confidence: 99%
“…GABA, like DA, was found to inhibit prolactin secretion at the adenohypophysial level [15,28,37,41]. This effect is probably mediated by high affinity receptors [14] which seem to act independently from DA receptors [11].…”
Section: Discussionmentioning
confidence: 95%